Different salves for different sores: international research remedies for a South African communication context - Greeff, W. J. (Department of Communication Science, University of the Free State, 2011)
A fact so widely accepted as to be considered common sense is that communication is influenced by the context in which it functions. It is for this reason that there is no single communication-related measurement scale suitable for all circumstances (Le Roux 2008: 264; Devlin 2003: 27). Yet, communication researchers continually make use of existing communication research methods in order to strengthen reliability and validity in research and to standardise measurement instruments for comparability of results. In most cases, these methods originate in the international arena. Le Roux (2008) proposed methods for adapting Communication Satisfaction and Relationship scales to the South African, third-world context specifically for use within the mining industry of South Africa. This article reports on a study testing Le Roux's (2008) adapted versions alongside those of the original questionnaires at the Gautrain project. The study confirmed Le Roux's adaptations, and adds additional recommendations for the distribution and administering of internationally generated questionnaires within the mining and construction industry of South Africa specifically, and the third-world context in general.
Keywords: Communication; Measurement; Standardisation